Masculinities in Contemporary Africa - Uchendu, Egodi (Book collections on Project MUSE., 2008)
"Although gender and non-gender scholars have studied men, such an academic exercise requires a critical and focused study of masculine subjects in particular social contexts, which is what this book attempts to do. This empirically rich collection of essays, the seventh of the CODESRIA Gender Series, deals with critical examinations of various shades and ramifications of Africa's masculinities and what these portend for the peoples of Africa and for gender relations in the continent. So much has changed in terms of notions and expressions of masculinities in Africa since ancient times, but many aspects of contemporary masculinities were fashioned during and since the colonial period. The papers in this volume were initially discussed at the 2005 month-long CODESRIA Gender Institute in Dakar. The contributors are gender scholars drawn from various disciplines in the wide fields of the humanities and the social sciences with research interests in the critical study of men and masculinities in Africa."--Book cover